HUBUNGAN ANTARA KARAKTERISTIK INDIVIDU, BEBAN KERJA MENTAL, PENGEMBANGAN KARIR DAN HUBUNGAN INTERPERSONAL DENGAN STRES KERJA PADA GURU DI SLB NEGERI SEMARANG - Amalia, Beki Rizki; Wahyuni, Ida; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Work Stress is form of a person's response both physically and mentally to a change in his environment that is disturbing and causing him to be threatened or uncomfortable. The purpose of this study was to analyze the association between individual characteristics, mental workload, career development and interpersonal relationships with work stress on teachers at SLB Negeri Semarang. This research type was explanatory research by using cross sectional approach. There were 36 teachers of mentally retarded students and teachers of deaf students as the pupulation in this research with sampling method. The data was collected by using NUT (National Union of Teacher) questionnaire, Nasa Tlx questionnaire, career development questionnaire and interpersonal relationship questionnaire. The statistic analysis was using chi square test. The results of statistic tests show that there was association between gender (p-value = 0,016), mental workload (p-value = 0,007), and interpersonal relationships (p-value = 0,053) with work stress on teachers. There was no relationship between age, employment and career development with work stress on teachers. The school should gave reward for exemplary teachers to improved the spirit of teaching, provide training to support teachers in teaching and conduct the regular sports activities to reduce stress levels that was caused by high workload.